YMCA Indian Guides Kite Flying Day at Woodward Park - Watkins, Howard::::::::: (1984)
Howard Watkins holding regular Benjamin Franklin kite by 6-foot round Yosemite Nation kite Howard wearing red Sierra Nation Indian Guides T-shirt